OPTIMIZATION OF DIAGNOSTICS AND MINIMALLY INVASIVE TREATMENT METHOD FOR SINUSITIS PATHOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Sinusitis remains one of the most common pathologies of the ENT organs found in clinical practice. According to the World Health Organization, every year about 15% of the world's population faces some form of this disease. Despite the development of drug treatments, many cases of sinusitis require surgical intervention to eliminate the cause of inflammation and restore the normal functioning of the paranasal Sinus pathology, which includes various forms of sinusitis, remains an urgent problem of modern medicine. Despite significant advances in pharmacotherapy, many cases require surgery for effective treatment. Traditional open surgery is associated with a high risk of complications and a long recovery. In this regard, endoscopic diagnostics and minimally invasive surgical techniques are becoming increasingly important due to their accuracy, minimal trauma and rapid recovery of patients. Traditionally used open surgeries, although effective, are associated with a number of disadvantages, such as high trauma, a long rehabilitation period and an increased risk of complications. In this regard, endoscopic diagnostics and minimally invasive surgical techniques are becoming increasingly popular among doctors and patients, as they offer a more gentle approach to the treatment of sinusitis.